Intraspecific and Interspecific Phenotypic Differences Confirm the Absence of Cryptic Speciation in Triatoma sordida (Hemiptera, Triatominae) - Garcia, Ariane Cristina Caris [UNESP]; de Oliveira, Jader [UNESP]; Cristal, Daniel Cesaretto [UNESP]; Delgado, Luiza Maria Grzyb [UNESP]; Bittinelli, Isadora de Freitas [UNESP]; Galvão, Cleber; Britez, Nilsa Elizabeth Gonzalez; Carrasco, Hernán José; da Rosa, João Aristeu [UNESP]; Alevi, Kaio Cesar Chaboli [UNESP] (American Society of Tropical Medicine and Hygiene, 2021)
Triatoma sordida is an endemic Chagas disease vector in South America, distributed in Brazil, Bolivia, Paraguay, and Uruguay. Chromosomal, molecular, isoenzymatic, and cuticular hydrocarbon pattern studies indicate cryptic speciation in T. sordida. Recently, T. rosai was described from specimens from Argentina initially characterized as T. sordida. Although several authors assume that the speciation process that supports this differentiation in T. sordida is the result of cryptic speciation, further morphological and/or morphometric studies are necessary to prove the application of this evolutionary event, because the only morphological intraspecific comparison performed in T. sordida is based on geometric morphometry and the only interspecific comparison made is between T. rosai and T. sordida from Brazil that evaluated morphological and morphometric differences. Based on this, morphological analyses of thorax and abdomen using Scanning Electron Microscopy and morphometric analyses of the head, thorax, and abdomen among T. sordida from Brazil, Bolivia, and Paraguay, as well as T. rosai, were performed to assess whether the evolutionary process responsible for variations is the cryptic speciation phenomenon. Morphological differences in the thorax and female external genitalia, as well as morphometric differences in the head, thorax, abdomen, pronotum, and scutellum structures, were observed. Based on this, the evolutionary process that supports, so far, these divergences observed for T. sordida populations/T. sordida subcomplex is not cryptic speciation. Moreover, we draw attention to the necessity for morphological/morphometric studies to correctly apply the cryptic species/speciation terms in triatomines.